129 Interim evaluation of a clinical educators pilot study via a multi-stakeholder online survey. Issue 12 (23rd November 2020) - Huynh, Chi; Hemavathi, Muniswamy; Aiello, Matthew; Clancy, Mike; Kennedy, Brian; Knox, Jane; Phillips, Eloise; Terry, David; Khan, Aanika; Rutherford, Graham; Symons, Helen; Chauhan, Veena; et al.
Abstract : Aims/Objectives/Background: In England, the demand for emergency care is increasing, confounded by challenges with recruitment and retention of multi-professional teams in Emergency Departments (ED). The intense working environment that clinical ED staff face is recognised as a cause of staff dissatisfaction, attrition and premature career 'burnout.' A new 'shop floor' Clinical Educator (CE) role may improve the retention and wellbeing of multi-professional ED teams. A Health Education England pilot developed and recruited CEs across 54 acute trust EDs in England, from 2017. Aston University and the Royal College of Emergency Medicine were jointly commissioned to undertake a service benefit evaluation. Methods/Design: An online survey was circulated to CEs, learners and managers across the 54 study sites. Each group answered questions relating to experiences, opinions and reflections. Topics included impact of a CE on patient flow, confidence and competence of staff, as well as sustainability and any impact on staff wellbeing. Results/Conclusions: Results: 314 individuals accessed the survey and 291 eligible respondents completed it, including: 187 learners, 65 CEs and 39 ED Clinical Directors/Managers. Learners (169/187), CE (63/65) and managers (39/39) saw no change/an improvement in patient flow. 100% of CEs felt that a CE in the ED improved competence and confidence of staff (88.2% of learners, 89.7% of managers). 7% (61/65) of CEs and 87.2% (34/39) managers agree that CEs have improved wellbeing of staff. 8% of managers (26/39) were unsure whether the CE role would be funded beyond the pilot, but 66.7% (26/39) strongly supported continuation of the CE role. Conclusion: Interim evidence suggests that CEs positively impact the multi-professional ED workforce.